Living Hadith: Praonan Tradition in Pasuruan Harbor City - Qur'ana, Faridah Amiliyatul; Hasyim, Muh. Fathoni (Diroyah : Jurnal Studi Ilmu Hadis, 2024)
Praonan is a tradition of the people of Pasuruan City that remains to this day, held on the seventh day of Idul Fitri, and is a source of understanding of the Hadith of Prophet Muhammad Saw at the level of field practice. This study used a qualitative method with a field study approach. Data collection was performed by observing and interviewing five people who were aware of the traditions of Praonan that originated in the three hadiths. This research intends to examine how the integration of Hadith and the praonan tradition and the content of values in the praonan tradition in the view of living hadith and social construction theory of Peter L. Berger and Thomas Luckmann. The findings of this research are as follows: (1) authentic Hadith history and Praonan traditions rooted in society are not contradictory but mutually synergistic and integrated; (2) Contains noble values that are beneficial to society until today, which are strengthening friendship, alms, and honoring the guests